Asymmetric Total Synthesis of Lobophopyranone A and B - Reddy, G. Sudhakar; Choudhury, Utkal Mani; Keerthana, H. Sai; Naik, K. Charan; Mohapatra, Debendra K. (Synthesis, 2024)
The first asymmetric total synthesis and structural confirmation of lobophopyranone A and B have been accomplished from commercially available starting materials. Reagent-controlled Keck–Maruoka allylation, Grignard reaction, chelation-controlled Sakurai allylation, and acid-mediated one-step TBS ether deprotection followed by cyclization are the crucial stages in this synthesis that create the 2,6-disubstituted dihydropyranone component.
Keywords: lobophopyranone; natural products; asymmetric synthesis; Keck–Maruoka allylations; Sakurai allylation; acid-mediated cyclization